Klippel -Trenaunay Syndrome: A Case Report - Paudel, U; Gupta, Sonia; Pant, A; Bagaria, R S; Shrestha, D P (Nepal Journal of Dermatology, Venereology & Leprology, 2012)
DOI: http://dx.doi.org/10.3126/njdvl.v10i1.6424 NJDVL 2012; 10(1): 49-52